The Gadget Phenomenon Among Elementary School Students - Nurjaman, Asep Rudi (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the impact of gadget use on primary school students' learning at SDN 3 Cinunuk. Interviews with teachers and students showed that gadget use has a multidimensional impact, both positive and negative, on students' concentration, physical health and social interaction. The use of gadgets can help students in understanding the subject matter, but it can also have negative impacts such as distraction and addiction. The use of gadgets can also affect students' development in cognitive, social, and emotional aspects. Therefore, proper supervision from teachers and parents is needed to ensure that gadget use supports children's learning and character development in a positive way. This study suggests that schools and parents need to work together to create a balanced and healthy learning environment, and provide digital education to students to use technology wisely and responsibly.